Continuous glucose monitoring by means of mid-infrared transmission laser spectroscopyin vitro - Vrančić, Christian; Fomichova, Anna; Gretz, Norbert; Herrmann, Carina; Neudecker, Sabine; Pucci, Annemarie; Petrich, Wolfgang (The analyst, 2011)
The continuous surveillance of glucose concentration reduces short-term risks and long-term complications for people with diabetes mellitus, a disorder of glucose metabolism. As a first step towards the continuous monitoring of glucose, reagent-free transmission spectroscopy in the mid-infrared region has been carried out in vitro using a quantum cascade laser and an optical silver halide fiber. A 30 μm gap in the fiber allowed for transmission spectroscopy of aqueous glucose solutions at a wavelength of 9.69 μm, which is specific to a molecular vibration of glucose. A noise-equivalent concentration as low as 4 mg/dL was achieved at an average power of 1.8 mW and an integration time of 50 s. This is among the most precise of glucose measurements using mid-infrared spectroscopy. Even with the very low average laser power of 0.07 mW the sensitivity of previous results (using a fiber optical evanescent field analysis) has been improved upon by almost one order of magnitude. Finally, the impact of potentially interfering substances such as other carbohydrates was analyzed.